Pemanfaatan E-Money dalam Transaksi Jual Beli Online di Era Digital Bagi Siswa SMA Negeri 6 Ambon - Anwar, Arman; Rahmadhani, Fitri; Mainake, Meilien Trivany; Assegaff, Syarifah Safina (Universitas Methodist Indonesia, 2024)
The use of E-money (electronic money) has become an important part of digital transactions in the modern era, especially in the online trading sector. This community service aims to provide education to students of SMA Negeri 6 Ambon regarding the use of e-money in facilitating online buying and selling transactions. Through the community service program held at SMA Negeri 6 Ambon, students are given an understanding of the use of e-money in everyday life. This activity also includes increasing digital literacy, the advantages and disadvantages of electronic money and its impacts. The results of this activity show an increase in students' understanding of non-cash transactions, their ability to use e-money for online transactions, and wiser financial management. Students also begin to recognize online business opportunities by utilizing e-money as a practical payment method. Overall, this community service brings students' readiness to face the rapidly growing digital economy. In the future, more direct practical sessions need to be implemented and an increase in understanding of digital security to minimize the risk of fraud in cyberspace.